Hexagon Fraud: Exploration of Academic Fraud in Accounting Students at Universities in Java, Indonesia - Dewa, Monica Malva Cakra; Maulana, Agus (Jurnal Riset Akuntansi dan Keuangan, 2024)
An accountant should be able to identify factors that can provide the results or impact of the decisions taken. Currently, an accountant's integrity is increasingly questioned. Habits can influence an accountant's integrity, one of which is behavior during their time as a student. This study aims to explore factors influencing students' engagement in academic dishonesty to mitigate such behaviors in the future. The study employs the theory of planned behavior and fraud hexagon theory to elucidate the motives behind academic fraud. The utilized method involves a quantitative approach processed through SmartPLS 3. This research was conducted with 247 accounting students at 34 universities in Indonesia. This research shows that pressure, ability, and collusion have a significant effect on academic fraud. Meanwhile, opportunity, rationalization, and ego have no effect on academic fraud. The findings of this research offer valuable insights for universities to formulate policies addressing the issue of academic fraud.